Anti‐VEGFR agents ameliorate hepatic venous dysregulation/microcirculatory dysfunction, splanchnic venous pooling and ascites of NASH‐cirrhotic rat. (2nd September 2013) - Yang, Ying‐Ying; Liu, Ren‐Shyan; Lee, Pei‐Chang; Yeh, Yi‐Chen; Huang, Yi‐Tsau; Lee, Wei‐Ping; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Lee, Fa‐Yauh; Tan, Tat‐Wei; Lin, Han‐Chieh
Abstracts Background & Aims Antivascular endothelial growth factor receptor (VEGFR) agents improve hepatic fibrosis and portal hypertension in cirrhosis. Detail interactions among recruited/activated leucocytes, hepatic angiogenesis and fibrogenesis, splanchnic blood pooling, decreased hepatic veins to fluctuated splanchnic blood volume (hepatic venous dysregulation), portal hypertensive syndrome and ascites have never explored in cirrhosis. Our study used two anti‐VEGFR agents – brivanib and sorafenib – to elucidate the relationship between above abnormalities of nonalcoholic steatohepatitis (NASH)‐cirrhotic rats. Materials and methods NASH‐cirrhotic rats received 2‐week brivanib, sorafenib or vehicle (NASH‐cirrhotic+briv, NASH‐cirrhotic+soraf and NASH‐cirrhotic rats) were included for various measurements. Results In comparison with NASH‐cirrhotic rats, significant decreased plasma VEGF, fibroblast growth factor, platelet‐derived growth factor, hepatic tumour necrosis factor (TNFα), IL‐1β, IL‐6, IL‐17 were accompanied by decreased leucocyte mass/activity (99 mTc‐phytate and 18F‐FDG SPECT/PET/CT scans), hepatic leucocytes recruitment/microvascular density (fluorescence‐enhanced intravital microscopy) and hydroxyproline content, and increased hepatic blood flow in NASH‐cirrhotic+briv and NASH‐cirrhotic+soraf rats. In addition, increased hepatic microvasculatures compliance‐related improved buffering effect of portal vein to acute mannitol infusion was associated with decreased circulating nitric oxide and aldosterone, plasma volume expansion (dye dilution method), splanchnic blood pooling (99 mTc‐RBC SPECT/PET/CT scans), peripheral hypotension, portal hypertension and ascites in brivanib and sorafenib‐treated NASH‐cirrhotic rats. Conclusion Besides antifibrotic, antiangiogenic and portal hypertensive effects, chronic antagonism of anti‐VEGFR with brivanib and sorafenib improves hepatic blood flow, hepatic venous dysregulation, inhibits leucocytes recruitment/activation, splanchnic blood pooling and ascites formation in NASH‐cirrhotic rats. Thus, brivanib and sorafenib might be ideal therapeutic agents in cirrhotic patients suffering from severe haemodynamic disarrangement and ascites.